Disappearing and reappearing differences in drug‐eluting stent use by race. Issue 2 (2nd December 2011) - Federspiel, Jerome J.; Stearns, Sally C.; Reiter, Kristin L.; Geissler, Kimberley H.; Triplette, Matthew A.; D'Arcy, Laura P.; Sheridan, Brett C.; Rossi, Joseph S.
Abstract Rationale, aims and objectives Drug‐eluting coronary stents (DES) rapidly dominated the marketplace in the United States after approval in 2003, but utilization rates were initially lower among African American patients. We assess whether racial differences persisted as DES diffused into practice. Methods Medicare claims data were used to identify coronary stenting procedures among elderly patients with acute coronary syndromes (ACS). Regression models of the choice of DES versus bare mental stent controlled for demographics, ACS type, co‐morbidities and hospital characteristics. Diffusion was assessed in the short run (2003–2004) and long run (2007), with the effect of race calculated to allow for time‐varying effects. Results The sample included 381 887 Medicare beneficiaries treated with stent insertion; approximately 5% were African American. Initially (May 2003–February 2004), African American race was associated with lower DES use compared to other races (44.3% versus 46.5%, P < 0.01). Once DES usage was high in all patients (March–December 2004), differences were not significant (79.8% versus 80.3%, P = 0.45). Subsequent concerns regarding DES safety caused reductions in DES use, with African Americans having lower use than other racial groups in 2007 (63.1% versus 65.2%, P < 0.01). Conclusions Racial disparities in DES use initially disappeared during a period of rapid diffusion and high usage rates; the reappearance of disparities in use by 2007 may reflect DES use tailored to unmeasured aspects of case mix and socio‐economic status. Further work is needed to understand whether underlying differences in race reflect decisions regarding treatment appropriateness.